Operationalization of the social cognitive theory to explain and predict physical activity in Germany: a scale development - Viktoria S. Egele; Robin Stark (Frontiers in Sports and Active Living)
IntroductionSocial cognitive theory is one of the most prominent psychological theories regarding human behavior. Previous research tested and confirmed parts of the theory concerning the explanatory and predictive value of the theory, both in specific populations and in selected domains of physical activity. However, the value of this research is limited as researchers often use their own item sets rather than validated scales. Therefore, comparability of the studies is restricted and the quality of the individual findings can often not be conclusively assessed as psychometric properties of the measurement are unclear. The goal of this research was to develop a parsimonious, reliable, and valid questionnaire to assess the elements of SCT in the context of physical activity.MethodsIn total, 90 items were developed for the four factors of SCT, which were then examined by exploratory factor analysis and reduced to 18 items in total.ResultsCross-validation was successful. Internal consistency was good for the four subscales, test-retest reliability was satisfactory, as were indicators for convergent and divergent validity.DiscussionA short, reliable, and valid instrument was developed intended for use in the general adult population in Germany for research on theoretical assumptions and interventions based on social cognitive theory.